EKONOMI KEMANDIRIAN BERBASIS KOPPONTREN - Daniar, Daniar (Islamic Economics Journal, 2013)
Islamic boarding school is a community-based institution, so that the culture and community culture give color to the values, spirit, and the school’s own philosophy. Beside, Islamic boarding school is obligated to be independent in every aspect, including in economic. Therefore, Islamic boarding school should establish the cooperation of Islamic boarding School (koppontren). The object of this research is Gontor Islamic boarding school, Ponorogo, who have koppontren business units since 1970. Data analysis was performed by reduction data, display data, and verification data. This research resulted in two conclusions. First, koppontren development model that includes koppontren management conducted independently by Kyai, teachers and the family of boarding school, business development patterns based on the needs of students and the public key, and the values of the broader education as the good of managing economic resources. The second, financial management system at the koppontren of Gontor boarding school be transparent, open, and is known throughout the family of boarding school, used only for the interests of the institution, and separate between individual rights and the right of the institution is clear.